ANALISA PENGETAHUAN PERAWAT PELAKSANA RUANG RAWAT JALAN TERHADAP TUGAS DAN WEWENANG SEBAGAI PEMBERI ASUHAN KEPERAWATAN DALAM KEGAWAT DARURATAN (IMPLEMENTASI UU KEPERAWATAN N0 38 TAHUN 2014) - Mona ariestia (Akper Kesdam I/Bukit Barisan Padang, 2022)
Law No. 38 of 2014 concerning nursing explains that each nurse's duties have their respective authorities. As a qualified nurse, knowing the duties and authorities of nurses according to law No. 38 of 2014 concerning Nursing in carrying out nursing practice is imperative to realize and improve optimal nursing services and improve health status. The aim of the research is to know the description of the knowledge of implementing nurses regarding the duties and authorities of implementing nurses as nursing care providers according to Law No. 38 of 2014. This type of research is quantitative with a descriptive study and a cross-sectional approach, proportional random sampling technique with a sample size of 88 people who are outpatient nurses stay. The results showed that most of the sample (66,7%) had good knowledge of nurses' duties according to Law No.38 of 2014 and most (62,9%) had poor knowledge of nurse's authority according to Law No.38 of 2014. Based on the research results, it is suggested that nurses better understand and increase their knowledge by reading about the duties and authorities of nurses according to Law No. 38 of 2014 concerning Nursing.